In situ and ex situ conservation: philosophical and ethical concerns - Rolston, Holmes, 1932-2025, author; Island Press, publisher (Colorado State University. Libraries, 2004)
Understandings of "natural" and "artificial" lie in the background of discussions about in-situ and ex-situ conservation. Plants growing ex-situ in botanic gardens are hybrids of the natural and the artificial. There will be temptations to substitute ex-situ for in situ conservation, believing this to protect the desired resource base. The intrinsic values in plants are ecosystemically situated. In this sense intrinsic plant value is in-situ. Removed to an ex-situ location, a plant--especially a domesticated or captive plant--becomes something else, compromised in its integrity. Such compromise may be pragmatically and politically necessary, but it needs to be recognized philosophically and ethically as prejudicing the values carried by plants.
Keywords: ecosystems; nature; conservation; wild; plants